Comparison of clinical signs and mortality rate in murine models infected with herpes virus isolates from captive wildlife - Allaudin, Zeenathul Nazariah; Nawi, Shahron; Hussein, Fuzina Nor; Tan, Seok Shin; Mohd Lila, Mohd Azmi (Veterinary Association Malaysia, 2011)
Clinical signs, cellular infectivity and mortality rate of two closely related alpha-herpesvirus from a gaur (UPMV5/05) and a bear(UPMVI9/05) were studied in mice experimentally infected via the nasal route. The grade of viral infection was divided into low (103 and 104 pfu/ml), medium (105 and 106 pfu/ml) and high (107 pfu/ml). Clinically, all animals with the exception of controls, showed respiratory and neurological sign starting from 36 hpi. Although there were a number of differences in the onset time of clinical signs, these were not significant and the types of clinical signs shown were common. Nevertheless, there was a significant difference in the mortality rate, in which isolate UPMVI9/05 from a bear was more pathogenic (83%) than the gaurisolate, UPMV5/05(16.7%). These results strongly suggest that the consequences of host adaptation of herpesviruses may have been derived from interspecies transmission and underscore the need for extreme caution when managing wild or captive animals in close proximity to bovines.